E-136 Overdue mechanical thrombectomy: a treatment for all strokes. (22nd July 2018) - Atallah, E; Hafazallah, K; Missios, S; Abbas, R; Tjoumakaris, S; Herial, N; Gooch, M; Rosenwasser, R; Zarzour, H; Jabbour, P
Abstract : Background and purpose: Decisions on the use of mechanical thrombectomy (MT) beyond 8 hours from onset of stroke symptoms remains fairly debatable. The adequate tools used for the triage of patients with acute ischemic stroke (AIS) symptoms has not been definitive yet. We studied the safety and the efficacy of delayed MT (>8 hours) with image-based selection criteria. Methods: Data of prospectively treated patients was retrospectively collected between 2010–2017. Data on intra-venous tissue plasminogen activator(IV-rtPA), National Institute Health Stroke Scale (NIHSS; range, 0 to 42) at admission, per-procedure complications (IA/IV-tPA after failed MT, distal embolus, vessel dissection, re-occlusion after MT), mortality, and clinical functional status evaluated with the modified Rankin Scale(mRS0–6) at latest follow-up was gathered. The primary outcomes were: (1) safety and the feasibility of delayed (>8 hours) MT, (2) functional independence on latest follow-up(mRS score <2), (3) functional improvement on latest follow-up defined as a de-escalation by one of the mRS score, and (4)overall mortality with delayed MT. Multivariate effects logistic regressions were conducted for statistical analysis. Results: Of 234 patients (average age 64.4 years, 45.3% female) that constituted our population, 215 were included in our statistical analysis: 137patients in the group of patients who received MT <8 hours from onset of symptoms(OS), and 78 others received MT beyond 8 hours from OS. 25/234 (10.7%) patients had tandem embolus. 81/234 (30.7%) patients performed their MT with just Second Generation Stent-Retrievers(SGSR), 16/234 (6.8%) patients received therapy with large-bore aspiration catheters, 135/234 (70.5%) patients received a salvage thrombus aspiration after failed first-line stent-retrievers thrombectomy. 89/234 (38%) patients had a first-pass successful vessel recanalization mTICI >2. The average time of revascularization was 92.2 min (SD=97.10). 27/234 (11.5%) had a mTICI of 2b, and 172/234 (73.5%) had a mTICI of 3. The average patient follow-up was 123 days(SD=163 days). MT beyond 8 hours was not a predictor of disability or functional deterioration, of increased mortality, of per-procedural complications, of successful vessel repermeabilization. However, delayed thrombectomy was linked to a higher length of post-procedural hospital stay. Conclusions: Patient selection for MT should not be primarily driven by time-based criteria. More objective dynamics such as image-based criteria should be further promoted as primary selection tools. Delayed MT after 8 hours should be a safe and highly efficacious first-line modality of treatment for strokes of anterior and posterior circulation. Disclosures: E. Atallah: None. K. Hafazallah: None. S. Missios: None. R. Abbas: None. S. Tjoumakaris: None. N. Herial: None. M. Gooch: None. R. Rosenwasser: None. H. Zarzour: None. P. Jabbour: None.